Herman Bavinck als "econoom": Een verkenning van zijn maatschappelijke geschriften - Hengstmengel, Joost (Theologia reformata, 2024)
The Reformed theologian Herman Bavinck (1854-1921) is known as a great dogmatist. Less well known is his lifelong interest in ethics and politics. This article focuses attention on Bavinck's largely unexplored socio-economic views. It examines his published and unpublished writings that revolve around the "social question" of poverty and unemployment. The article concludes that, rather than a hobby, Bavinck's attention to socioeconomic issues was entirely consistent with his conception of doing theology. Meanwhile it raises the question how Bavinck's "Christian-historical" view of society and economy fit into his theology as a whole.